Evaluasi Tata Kelola Sistem Kehadiran Perkuliahan di Universitas X Menggunakan COBIT 2019 DSS02 - Abdi Nurhaqqin; Auzan Abrar Alrafi; Julfa Irnanda Pratiwi; Tikno (Universitas Komputer Indonesia, 2026)
University X utilizes a digital attendance system to support academic service efficiency. However, the effectiveness of IT incident and service request handling in the system still requires measurable evaluation due to data synchronization issues and delays in complaint handling responses. This study aims to evaluate the capability level of IT service governance in the attendance system using the DSS02 (Managed Service Requests and Incidents) domain of the COBIT 2019 framework. The research method employs a descriptive quantitative approach by collecting data from 5 ICT University X unit respondents as the internal service providers through questionnaires and observations. The evaluation results show that the current average capability level is at Level 3 (Established) with a score of 3.68. Gap analysis reveals that although operational processes are formally standardized and documented, there are still weaknesses in incident closure communication and proactive service performance monitoring. The proposed recommendations include developing an automated notification system and integrating reporting platforms to minimize the gap toward the target level. This research is expected to serve as a strategic reference for enhancing IT governance in alignment with university operational needs. Keywords – Attendance System; Capability Level; COBIT 2019; DSS02; ICT University X.